An Investigation of the Effectiveness of Scaffolding Strategies in EFL Libyan Classrooms - Wafa Ali Abdelrazg Mktad (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
This research paper aims to investigate the effectiveness of scaffolding in teaching English as a foreign language. This topic is a very important one in psychology and education. This concept of scaffolding is related to the work of Lev Vygotsky; sociocultural theory that is produced in (1934). Generally, Scaffolding is a teaching method that aims to support learners by enhancing language communication skills, and boosting confidence in learning. Data collected by questionnaire based on Likert scale of assessing, and semi structured interview that is consisted of group of open ended questions. Study conducted in Libyan context with both Libyan EFL teachers and EFL students at the college level. The result confirms the effectiveness of scaffolding instruction, since scaffolding is a valuable technique that can be used successfully. However, overcoming its potential drawbacks is crucial to avoid major challenges in classroom application. These drawbacks are primarily related to inadequate acknowledgement, ineffective class-management, and insufficient positive feedback. After investigation, it become very clear that any instructional approach needs to be justified to ensure compatibility with the intended academic purpose, as well as any application of theories or methods in instruction requires thorough preparation and training to achieve its full potential any efficiency.